Exploring influences on pharmacists’ and students’ ethical reasoning in a changing practice landscape in Australia - Sim, T.; Sunderland, B.; Hattingh, H. Laetitia (Springer Netherlands, 2018)
© 2018, Springer Nature Switzerland AG. Background Practising pharmacists continuously develop their ethical reasoning skills, which evolve with practice experience and exposure to challenging scenarios. Considering the recent expansion of the roles of pharmacists and the paradigm shift in pharmacy practice, it is timely to explore community pharmacists’ attitudes regarding the importance of ethics and their ethical reasoning. Objective To explore underlying factors influencing community pharmacists’ and pharmacy students’ ethical reasoning and attitudes towards pharmacy ethics, ethical reasoning processes and perceived current dilemmas. Setting Practising registered community pharmacists, pharmacists with provisional registration (interns) and final year pharmacy students in Australia. Method Two focus group discussions and two interviews were conducted with 16 Western Australian community pharmacists, interns and students. Participants were purposively selected for gender, background, practice setting, and practice experience. Main outcome measure Emerging themes embracing important influences on community pharmacists’, interns’ and students’ ethical reasoning and perceived current ethical dilemmas and challenges. Results Two major themes embraced participants’ ethical reasoning processes and conduct: (1) fundamental underpinning, from personal values and practice exposure, and (2) paradigm influenced, such as the changing healthcare landscape, expansion of roles, management of dilemmas, and competence. Increased frequency and complexity of ethical dilemmas related to role expansion. Rural pharmacists experienced unique ethical dilemmas in relation to practice isolation, privacy and confidentiality. Conclusion Changes in the community pharmacy practice environment has increasingly exposed pharmacists to more complex ethical dilemmas. Pharmacists practising in rural communities experience unique challenges. Structured and sound ethical reasoning skills are essential as pharmacists are faced with contemporary challenges.